2023
DOI: 10.1186/s12864-023-09117-7
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to dietary linalool primarily involves co-expression of cytochrome P450s and cuticular proteins in Pagiophloeus tsushimanus (Coleoptera: Curculionidae) larvae using SMRT sequencing and RNA-seq

Abstract: Background Pagiophloeus tsushimanus (Coleoptera: Curculionidae), an emerging forest pest exclusively infesting camphor trees, has recently caused severe ecological and economic damage in localized areas in China. Its population outbreak depends largely on the capacity to overcome the pressure of terpenoid-derived metabolites (e.g. linalool) from camphor trees. At present, the molecular basis of physiological adaptation of P. tsushimanus to dietary linalool is poorly understood, and there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…These rapid expansion families included those responsible for cuticle formation (cuticular protein: 17; chitin-binding type-2 domain-containing protein: 15; insect cuticle protein: 7), detoxification metabolism (glutathione S-transferase: 14; cytochrome P450: 5), digestion (trypsin: 11), juvenile hormone synthesis (farnesyl pyrophosphate synthase: 9), chemosensation (gustatory receptor: 8; PBP/GOBP family: 8; odorant receptor: 5), immunity (cecropin family: 7), and so on ( Table S10 , Figure 1 b). We speculate that these expanded families are related to foraging and adaptation to the host plant, as terpenoid-derived metabolites in Lauraceae trees, such as linalool, have recently been reported to act on the expressions of cuticular proteins and cytochrome P450s simultaneously [ 80 ]. The GO and KEGG enrichments of the rapid expansion families further indicate that their functions are involved in detoxification, metabolism, alarm pheromone, and some functions regarding biological processes for which we could not discover the specific meaning ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…These rapid expansion families included those responsible for cuticle formation (cuticular protein: 17; chitin-binding type-2 domain-containing protein: 15; insect cuticle protein: 7), detoxification metabolism (glutathione S-transferase: 14; cytochrome P450: 5), digestion (trypsin: 11), juvenile hormone synthesis (farnesyl pyrophosphate synthase: 9), chemosensation (gustatory receptor: 8; PBP/GOBP family: 8; odorant receptor: 5), immunity (cecropin family: 7), and so on ( Table S10 , Figure 1 b). We speculate that these expanded families are related to foraging and adaptation to the host plant, as terpenoid-derived metabolites in Lauraceae trees, such as linalool, have recently been reported to act on the expressions of cuticular proteins and cytochrome P450s simultaneously [ 80 ]. The GO and KEGG enrichments of the rapid expansion families further indicate that their functions are involved in detoxification, metabolism, alarm pheromone, and some functions regarding biological processes for which we could not discover the specific meaning ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, an interesting phenomenon found during early indoor and eld observation is that P. tsushimanus always has a special preference for C. camphora to other Lauraceae trees (Li et al, 2021). However, it is di cult to establish a stable population on close species (Li et al 2019). At present, the mechanism of host identi cation and location of this pest and key phytochemicals in above process are still unclear.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, rapid and remarkable developments in sequencing technology and increasing numbers of complete insect genomes have opened up new avenues for exploring global transcriptome changes reflecting the physiological state of insect pests to plant metabolites exposures, unveiling previously unknown mechanisms and mining functional genes (Lin et al, 2023;Li et al, 2023). Huang et al (2018) used RNA-Seq and qPCR to characterize the expression levels of detoxification genes, especially P450 genes in Sitophilus zeamais responding to terpinen-4-ol, the main constituent of Melaleuca alternifolia essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2018) used RNA-Seq and qPCR to characterize the expression levels of detoxification genes, especially P450 genes in Sitophilus zeamais responding to terpinen-4-ol, the main constituent of Melaleuca alternifolia essential oil. Li et al (2023) analyzed transcriptome profiling of linalool-exposed Pagiophloeus tsushimanus larvae using RNA-seq and single-molecule real-time sequencing. Gene ontology enrichment of DEGs revealed that overall upregulation of DEGs encoding cytochrome P450s and cuticular proteins was the primary response characteristic in larvae upon exposure to linalool.…”
Section: Introductionmentioning
confidence: 99%